Decolonizing humans, ending gender abuse, and sexual violence, from discovery to the twenty-first century and beyond - Myers, Larry (My University, 2022)
To understand “Decolonizing Humans, Ending Gender Abuse, and Sexual Violence, from Discovery to the Twenty-First Century and Beyond.” We will look at the mechanisms from time immemorial to the present that that buoy colonialism and imperialism in our country today. This thesis will briefly examine how America’s Indigenous Peoples and communities have pushed back against colonialistic and imperialistic mechanisms in the 20th and 21st centuries by exposing the harsh truths that have greatly diminished the Indigenous populations across the country. This thesis focuses on Missing and Murdered Indigenous Women [MMIW] and looks at how we have arrived at this long-standing travesty to understand how through the efforts of social and political activism, Indigenous people and organizations have been able to educate and inform the general population. We will examine the policies and laws that have allowed the states and federal government to systematically remove Indigenous children from their homes. Unscrupulously coerced thousands of Indigenous women of childbearing age into sterilizations while lying to thousands more about operations that also resulted in sterilizations without the knowledge of adolescent females, and women, young and old. Finally, we will conclude this thesis by examining how we may approach the difficult process of dismantling the mechanisms of settler colonialism, and imperialism to address the violence perpetrated on Native America women, Native communities, as well as all people of color that have been subjected to centuries of sexual assault and violence to divest them from sovereignty, liberty, resources and life.
Keywords: MMIW Sexual Violence Colonialism Imperialism